KONSEP HUKUM HAK DAN KEWAJIBAN WARGA NEGARA PERSPEKTIF PIAGAM MADINAH - Syarif, Nawaz; Habibi, Ahmad (Mitsaqan Ghalizan, 2024)
In the course of history, we have seen that conflict occurs due to different needs, which is why sometimes the law appears as a way to mediate between one another. In this case, the Medina Charter, which is the state Constitution, is the legal basis regarding the rights and obligations of its people. This research is legal research which focuses on analyzing using a conceptual approach how the legal concept of the Medina Charter presents the rights and obligations of every human being as a citizen. The Medina Charter teaches us lessons about Brotherhood (Al-Ikha), Equality (Al-Musawa), Tolerance (Tasamuh), Deliberation (Al-Tasyawur), mutual help (Al-Ta'awun), Justice (Al-Aku). The points given here play a very important role in life in society, for example the brotherhood that is given will form a bond that requires other people to respect and appreciate each other's fellow human beings. Brotherhood also creates peace because they feel a bond. The equality provided in the Medina charter also brings us to the same position without having to differentiate, and this also makes tolerance happen in people's lives